THE STRUGGLE AND THE EFFECTS OF BEING TRANSGENDER AS DEPICTED IN JULIE ANNE PETERS’ LUNA - ABIDATI, ALVITA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Transgender is a gender identity disorder. To be accepted by the societythat believes gender stereotypes of both male and female, transgender tries to be the opposite gender by changing his or her appearance. Unfortunately, many of them are still getting alienated and mocked. These treatments surely affecttransgender psychology such as feeling depressed and committing suicide. In this study, the researcher identifies how is the struggle of transgender in dealing with negative treatments from the society and the effects of those treatments toward his psychological condition, as represented by Luna, in Julie Anne Peters’ Luna.This research uses qualitative method because it is aimed to analyze andexplain the meaning of the message inside the novel. Therefore, by usingqualitative design of research, the writer needs to collect the text from the novel to be analyzed. The study uses sociological approach and queer theory to help the writer understands more about transgender. The writer also uses psychological approach and mood disorder concept to analyze the psychological effects of society negative treatments toward transgender psychology, represented by Luna.The result of the study shows that Liam is a transgender, named Luna. Every time he comes out as Luna, she gets some negative treatments such as bullying, mocking, transphobia and harassment. These treatments affect Liam’spsychology and make him feels depressed and thinks of committing suicide.However at the end, Liam, can encourage himself after meeting anothertransgender who supports him to be transgender and to do sex reassignmentsurgery. Gradually he has her new identity developed.For the next researchers, the writer suggests the use of transgender themeand queer theory as an approach can be applied in another novel and the othergenres of literary works to enrich the study of queer gender and sexuality in theliterature.Keywords: transgender, society, depression, mood disorder.